Efficacy and Non Invasive Treatment of Sialorrhea in the Goldenhar Syndrome - Marvulli, Riccardo; Gallo, Giulia A.; Mastromauro, Lucia; Dicuonzo, Franca; Fiore, Pietro; Ianieri, Giancarlo; Megna, Marisa (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2018)
Background and Objective: Goldenhar syndrome (ocular-auricular-vertebral syndrome), a rare congenital condition arising from defects in the first and second brachial arches, consists in clinical variety of features ranging from facial abnormalities, ear-eye abnormalities, vertebral defects and congenital heart problems and severe obstructive sleep apnea. Due to craniofacial abnormalities, patients presents mechanical obstructive phenomena and sialorrhea that cause prone position, language’s fastening, use of nasopharyngeal cannulas and tracheal intubation. Methods: In this article, we report a case of a 16 years old child affected by Goldenhar syndrome and sialorrhea to demonstrate improvement of the daily patient management, through inoculations of botulinum toxin type A. Due to severe sialorrhea which caused tracheobronchial daily aspirations, the caregivers used an external aspirators. Results: In the first infiltration (August 2016) the parotid and submandibular glands bilaterally were inoculated with incobotulinum toxin type A (Xeomin®, Merz Pharma) with dosages of 5 UI for each of them, for a total of 20 UI without clinical efficacy (no quantitative and qualitative saliva reducing during 3 months). In the second (November 2016) and third (February 2017) infiltrations each parotid and each submandibular glands were injected with a (dosage of 7 UI and 5 UI respectively (total of 24 UI of incobotulinumtoxin A) with important clinical results (saliva production and tracheo-bronchial aspirations reduced). Conclusion: Therefore, botulinum toxin type A could be a good and non invasive treatment of sialorrhea in Goldenhar syndrome to improve oral hygiene and daily patient management.
Keywords: Goldenhar syndrome